Modern views on the problem of hypertension in teenagers - S. N. Malakhova (Zaporozhye State Medical University, 2014)
Aim. The literature review is devoted to the actual problem of modern medicine - hypertension in teenagers. Numerous scientific studies have allowed identifying risk factors for the disease. Heredity, low physical activity, overweight, early puberty, metabolic disorders, bad habits, increased intake of salt are the most studied. In the last decade the role of molecular genetic markers of hypertension was proved. Among them, gene polymorphism of angiotensin converting enzyme, angiotensinogen gene, the gene of vascular angiotensin receptor II, endothelial dysfunction are the most studied. Conclusion. Given the fact that in most teenagers the disease is asymptomatic, it is necessary to examine adolescents with risk factors for the disease more carefully, with the subsequent development of non-drug measures of correction.